EVALUASI KINERJA PERTUMBUHAN LOBSTER AIR TAWAR Cherax quadricarinatus YANG DIPELIHARA DENGAN FEEDING RATE BERBEDA - dudi lesmana; Robin; Novita MZ; Amalia Nur Milla; Mulyana; Amri Priyadi; Yuni Puji Hastuti (Universitas Djuanda, 2022)
One of the obstacles faced in the cultivation of freshwater crayfish , especially in enlargement is the right feeding rate that can improve growth performance. This study aims to evaluate the growth performance of freshwater crayfish with different feeding rates. This research was conducted in Cicareuh Village, Cikidang District, Sukabumi Regency. with 3 treatments, namely feeding rate 1%, 2.5%, and 4% for 40 days. Parameters observed in this study were specific growth rate, absolute weight growth rate, absolute length growth, absolute weight growth, feed efficiency, survival and water quality. This study was analyzed by ANOVA and Tukey's further test. In general, different feeding rates have a significant effect on growth performance and FR 4% is the best feeding rate in this study.